2021
DOI: 10.1111/bjdp.12401
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of adolescent stressful life events and young adults’ socioeconomic and relational outcomes: Weight and depressive symptoms as mediators

Abstract: Little is known about how biological and psychological consequences of adolescent stressful life events (SLEs) are jointly associated with socioeconomic and relational outcomes in adulthood. To address this gap, the present study involved testing a model based on the life course perspective that posits adolescent SLE trajectories produce parallel trajectories of depressive symptoms and weight status, which are jointly associated with socioeconomic status and intimate relationship quality in adulthood. Prospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 74 publications
0
7
0
Order By: Relevance
“…The influence of parental rejection may be attributed to the erosion of psychological and cognitive resources, such as self‐esteem, mastery, future orientation and social relations (Rohner & Bitner, 2002). In particular, youth who are rejected by parents are especially likely to feel worthless, pessimistic about the future, and lack future orientation and are more likely to experience disrupted economic and educational achievement during the transition to adulthood, leading to disease risk in YA (Rohner & Bitner, 2002; Wickrama, Klopack, & Sutton, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The influence of parental rejection may be attributed to the erosion of psychological and cognitive resources, such as self‐esteem, mastery, future orientation and social relations (Rohner & Bitner, 2002). In particular, youth who are rejected by parents are especially likely to feel worthless, pessimistic about the future, and lack future orientation and are more likely to experience disrupted economic and educational achievement during the transition to adulthood, leading to disease risk in YA (Rohner & Bitner, 2002; Wickrama, Klopack, & Sutton, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…This underlying pathological process is likely produced, in part, as a response to a social stressor (e.g., parental rejection), which activates the brain regions that react to stress experiences (Chou et al, 2016). Comorbid depressive symptoms and chronic pain may also increase the risk of impaired socioeconomic attainment in YA (Wickrama, Klopack, & Sutton, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2011, Chinese scholars used the longitudinal data of 6970 Chinese adolescents to construct LGCM to analyze the change trajectory of psychological distress symptoms and BMI and their correlation; the results showed no significant correlation (59). A study of 11,677 US adolescents constructed linear trajectories of SLEs and BMI, showing the early co-development but a small correlation coefficient (38). However, other studies have questioned the linear trajectory of BMI because of the long age spans of children, diet, experience, or pubertal development; the piecewise LGCM was used, and the results showed no co-development in children aged 3 to 7 years, but the slope of BMI and internalizing symptoms was correlated in children aged 7 to 14 years, suggesting that cross-domain time pathways may emerge in mid-childhood as social, physiological, and psychological processes begin to play an increasingly important role in these health outcomes (60).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that a higher cumulative number of SLEs increased the likelihood of developing mental health problems [11][12][13]. Various studies suggested that the number of accumulated SLEs experienced at a point in time, as well as an increase or decrease of SLEs over time could affect young adults' mental health [14,15]. However, life-course studies with multiple time-points are scarce, especially those that cover trajectories of accumulated SLEs throughout the full adolescence and change in mental health in young adulthood.…”
Section: Introductionmentioning
confidence: 99%